Analysis of the Influence of the Use of Information Technology and Knowledge Management on Employee Performance with Motivation as an Intervening Variable (Studies in the Regional Government of Sidoarjo Regency) - Fita Fitria Lestariana; Sigit Hermawan (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine and analyze the influence of Information Technology Utilization and Knowledge Management on Employee Performance with Motivation as Intervening Variables in the Regional Government of Sidoarjo Regency. The analytical tool used in the form of a questionnaire distributed to 100 employees in 15 sub-districts in Sidoarjo regency with the results of the use of Information Technology has a significant effect on motivation; knowledge management has a significant effect on motivation; the utilization of Information Technology and knowledge management simultaneously have a significant effect on motivation; Information Technology utilization has a significant effect on employee performance; knowledge management has a significant effect on employee performance; motivation has a significant effect on employee performance and the use of Information Technology and knowledge management has a direct and significant effect on employee performance through motivation.